Kazakh national pedagogy in the upbringing of boys - Yenilkhan Kozybayev, Gulshat Кulabekova,; Talgatbek Ayazbaev, Aigul Kurmanbekova, Zhanat Sarybekova, (Opción, 2019)
This article is paid special attention to the problems of national pedagogy, traditions of family upbringing, and the specifics of the upbringing of boys on the basis of the Kazakh national pedagogy via theoretical analysis of scientific and pedagogical literature. As a result, the Kazakh national pedagogy in combination with modern, new traditions serves to the nationwide upbringing and education of the young generation. In conclusion, the national pedagogy which does not lose the importance eventually should be considered the integral link of the upbringing system.